Headteachers’ Perception of the Implementation of the Capitation Grant Scheme In The Sunyani West District of the Brong Ahafo Region (International Journal of Scientific Research and Management (IJSRM), 2019)
This study was conducted to find out head teachers’ perception of the implementation of the capitation grant scheme in Sunyani West East District of the Brong Ahafo Region. The study specifically focused on explaining how head teachers conceptualised the concept of capitation grant scheme, the implementation process, and the challenges associated with the implementation of the scheme. A descriptive research design was adopted for the study, and a questionnaire and an interview guide were designed and administered to a sample of 40 head teachers from the district in the Region. The analysis of data revealed that 70.0% of thehead teachers had an in-depth understanding of the source of capitation grant as being from the Government. The study, among others, found that the main challenges confronting the smooth implementations of the scheme were delay in the release of funds and inadequate funds. It is recommended that Government should release adequate amount of the grant in good time (thus, before the beginning of each quarter) so that school heads will avoid pre-financing of school activities. Also, the Ghana Education Service should continue to train head teachers in financial management and administration for prudent use of funds.